1977
DOI: 10.1525/ae.1977.4.1.02a00020
|View full text |Cite
|
Sign up to set email alerts
|

ecological niche theory in sociocultural anthropology: a conceptual framework and an application1

Abstract: The concept of “ecological niche” is frequently employed in sociocultural anthropology, but there have been few systematic applications of it. This paper examines the utility of the concept for the analysis of social interaction and change, with special reference to complex societies. In a small agricultural valley of northern California, competition between two status groups over a scarce resource—land—has led to displacement and changing patterns of resource use. “Niche” describes the aggregate outcome of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Further, the cropping or livestock enterprises that farmers pursue depend in part on the climate and the quality of their land (Galdwin 1980;Love 1977). In Almond Valley, California, Love (1977) showed that the combination of soil distribution, topography, favorable access to irrigation water, and original land tenure patterns produced a niche of smaller than average farm sizes and a dispersed settlement pattern. Kentucky, like Almond Valley, has a varied soil profile in association with differences in topography.…”
Section: Ecological Factorsmentioning
confidence: 99%
“…Further, the cropping or livestock enterprises that farmers pursue depend in part on the climate and the quality of their land (Galdwin 1980;Love 1977). In Almond Valley, California, Love (1977) showed that the combination of soil distribution, topography, favorable access to irrigation water, and original land tenure patterns produced a niche of smaller than average farm sizes and a dispersed settlement pattern. Kentucky, like Almond Valley, has a varied soil profile in association with differences in topography.…”
Section: Ecological Factorsmentioning
confidence: 99%
“…While each musician's socio-musical affinities are registered in their personal style, so too are aspects of their psychological makeup. Sometimes, it can seem that a musician's essentialised personality, as extrapolated from others' encounters, is reflected within their musical outputas with Beethoven and other semi-mythologised characters for example 10 The present authors are surprised that so few ethnomusicologists have thought to apply a niche theory perspective to the exploration of musical style formationdrawing from the pioneering works of cultural ecology (Steward [1955(Steward [ ]1990Barth 1956;Rappaport 1968) and from later developments (for example, Love 1977;Alley 1982;Kendal 2012). We particularly advocate the application of niche construction theory (NCT), which addresses the previous unfortunate tendency to underplay individual agency in evolution-related conceptualisation (see Rahaim 2006: 35, 36); now organisms are seen to not only respond to but also modify their niches through processes of negotiation (Odling-Smee, Laland and Feldman, 2003).…”
Section: Towards a Model Of Personal Style Formation And Expressionmentioning
confidence: 83%
“…Matthew Kearns and Simon Reid Henry use the term in a way similar to our own in their excellent paper on vital geographies (Kearns and Reid-Henry, 2009). The term has become popular in socio-cultural anthropology since the 1970s, though seldom with detailed conceptual considerations, despite the hopes of Thomas Love (1977). As we shall see, some link the idea of the niche with arguments about human evolution (Fuentes, 2016), 9.…”
Section: Orcid Idsmentioning
confidence: 99%